Microgel Particle Collision with Smooth and Nanofiber Hydrophobic Surfaces during Three-Dimensional Printing of a Biopolymer Layer; Langmuir; Vol. 39, iss.25 - Piskunov M. V. Maksim Vladimirovich; Khomutov N. A. Nikita Andreevich; Piskunova A. E. Aleksandra Evgenjevna; Di Martino A. Antonio; Khan E. A. Elena Alekseevna; Bolbasov E. N. Evgeny Nikolaevich (2023, 2023)
Title screen